The Influence of Academic Independent Directors and Confucianism on Carbon Information Disclosure: Evidence from China. (5th March 2021) - He, Ren; Zhou, Mingdian; Liu, Jing; Yang, Qing
Abstract : As global warming has received widespread attention, the disclosure of firms' carbon information has been expected by increasing stakeholders. This study extends the previous literature on the determinants of firms' carbon information disclosure by examining the influence of academic independent directors and Confucianism on the quality of carbon information disclosure. Using a sample of Chinese listed firms in the CSI 300 Index during the period of 2012–2018, our empirical results show that academic independent directors have a significantly positive association with the quality of carbon information disclosure. The results also reveal that Confucianism positively affects the quality of carbon information disclosure. Moreover, Confucianism positively moderates the relationship between academic independent directors and the quality of carbon information disclosure. The results imply that Confucianism, as an informal system, can promote the governance effect of academic independent directors on firms' carbon information disclosure behaviour. Our findings offer shareholders, regulators, and other stakeholders an integrating perspective on motivating firms to disclose high quality carbon information.